Diagnostic Approach of Mesenteric Cyst in Children: A Case Report - Purnama, Asep Aziz; Oswari, Hanifah (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Mesenteric cysts are intra-abdominal masses that arise from obstructed lymphatic drainage within the mesentery. Early diagnosis can be challenging, as it is often difficult to recognize based solely on clinical findings. The diagnosis is frequently made following imaging studies or during surgery. Despite their generally benign nature, delayed diagnosis can lead to serious complications. This case report aims to share our experience on the diagnostic approach for mesenteric cysts in children. Case: A 2-year-old boy presented with a 14-month history of slowly progressive abdominal distension and signs of bowel obstruction, including weight loss. Abdominal ultrasound revealed thin-walled, well-demarcated, septated fluid sacs consistent with a cyst. Abdominal CT-Scan showed massive ascites filling the intraperitoneal cavity and pushing the intestine upward along the thickened mesentery, causing bowel obstruction. Histopathological examination confirmed the diagnosis of cyst lymphangioma derived from mesentery. The cyst was successfully excised via laparotomy, and histological examination confirmed it as a cystic lymphangioma. Discussion: Our diagnostic approach focused on exclusion of differential diagnosis for abdominal distention in children, including ascites, abdominal tuberculosis, mesenteric cysts, and intra-abdominal masses. The absence of constitutional symptoms and lack of response to anti-tuberculosis therapy made it an unlikely diagnosis. While the CT-scan suggested ascites, the ultrasound results suggested a mesenteric cyst. Despite its large size, a complete excision of the cyst was successfully performed via laparotomy. Conclusion: The nonspecific nature of mesenteric cysts often delays diagnosis, making abdominal ultrasound an essential initial imaging modality for patients suspected of having this condition.